2019
DOI: 10.1042/cs20190180
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced type 2 diabetes impairs neurological recovery after stroke in correlation with decreased neurogenesis and persistent atrophy of parvalbumin-positive interneurons

Abstract: Type 2 diabetes (T2D) hampers stroke recovery though largely undetermined mechanisms. Few preclinical studies have investigated the effect of genetic/toxin-induced diabetes on long-term stroke recovery. However, the effects of obesity-induced T2D are mostly unknown. We aimed to investigate whether obesity-induced T2D worsens long-term stroke recovery through the impairment of brain’s self-repair mechanisms – stroke-induced neurogenesis and parvalbumin (PV)+ interneurons-mediated neuroplasticity. To mimic obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 83 publications
(134 reference statements)
6
60
0
Order By: Relevance
“…The positive effects mediated by Ex-4 in stroke recovery could also be mediated by indirect (via glycemia regulation and normalization of insulin resistance) or direct effects occurring in the brain. Interestingly, we show that Exe-4 treatment reversed T2D-induced PV + interneuron atrophy (42). PV + interneurons play key role in neuronal plasticity and thus could have signi cant effects on neurological recovery after stroke (55,56).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The positive effects mediated by Ex-4 in stroke recovery could also be mediated by indirect (via glycemia regulation and normalization of insulin resistance) or direct effects occurring in the brain. Interestingly, we show that Exe-4 treatment reversed T2D-induced PV + interneuron atrophy (42). PV + interneurons play key role in neuronal plasticity and thus could have signi cant effects on neurological recovery after stroke (55,56).…”
Section: Discussionmentioning
confidence: 69%
“…3a). We have previously shown that shortly (2 weeks) after stroke the soma volume of PV + interneurons is decreased in the peri-infarct region of the striatum and, while in Non-T2D mice the soma volume recovers back to normal within 6 weeks after stroke, this atrophy persists in T2D (42). In the present study, potential differences in stroke-induced atrophy of PV + interneurons were also assessed by measuring the soma volume of these neurons in the contralateral and ipsilateral periinfarct striatum.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations